The Etiology of Chest Pain in Children Admitted to Cardiology Clinics and the Use Echocardiography to Screen for Cardiac Chest Pain in Children - Li Chen; Hongzhou Duan; Gang Li; Xiaoyan Li (Frontiers Media S.A., 2022)
AimsChest pain is a common disease in children. Most cardiac specialists use echocardiography to evaluate the etiology of and screen for children's cardiac chest pain. We analyzed the etiology and echocardiography results of children with chest pain in pediatric cardiology clinics, clarified the disease spectrum and evaluated the diagnostic value of echocardiography in screening cardiac chest pain in children.Methods and ResultsThe clinical data of children with chest pain aged younger than 18 years who admitted to the pediatric cardiology clinic of Beijing Anzhen Hospital between 2005 and 2019 were analyzed. The patients were divided into three groups, including the preschool group, the school-age group and the adolescent group. Total 3,477 children were enrolled in this study. 232 (6.7%) patients were caused by cardiac diseases and chest pain was of non-cardiac origin in 3,245 patients (93.3%). The incidence of non-cardiac chest pain in the adolescent group was significantly lower than the other two groups, respectively (91.4 vs. 94.9 vs. 94.3%, P < 0.05). In the preschool group, most of the patients were girls (51.4%), while in the school-age group and the adolescent group, most of the patients were boys (P < 0.05). Among the children (n = 3,205) who underwent echocardiography, 108 children had positive results, and 3,097 children had negative results. Among the 108 positive results, 10 cases of cardiac diseases were related to chest pain. The sensitivity, specificity of echocardiography in the diagnosis of cardiac chest pain were 6.7, and 96.9%, while the positive predictive value and negative predictive value was 12.96 and 93.67%, respectively.ConclusionIn children with chest pain who are admitted to pediatric cardiology clinics, chest pain is mostly benign and rarely due to cardiac diseases. The use of echocardiography in evaluating cardiac chest pain in children is of little diagnostic value and leads to excess costs for patients and the health care system.